Capacitação e rede de apoio à cuidadores informais de idosos como suporte integral às práticas assistenciais no domicílio. - Colturato, Simone Ramos Alvarenga. [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Introduction: The proportion of elderly people in Brazil has been growing considerably, and the demographic and epidemiological transition triggers several demands in the practice of home care for the elderly. In this context, the figure of the informal caregiver emerges, who is not always trained to perform this function and faces emotional and physical strain, causing a significant burden on their daily lives. Objective: This work aimed to understand the needs of informal caregivers of the elderly in order to offer health education in virtual learning environments. Methodology: This study corresponded to a development study and was elaborated based on the qualitative method through Bardin's Content Analysis, directed at informal caregivers of the elderly in the city of Itapeva-SP and the general public, who participated in the geriatrics outpatient clinic of the Itapeva-SP Elderly Reference Center (CRI). The research was developed in 5 stages: 1- Definition of the themes identified in the practice of elderly care through qualitative analysis; 2- Construction of a didactic-pedagogical project for the virtual course "Informal Caregiver of the Elderly"; 3- Making the course available to informal caregivers in the municipality of Itapeva-SP and the general public; 4- Creating a website/app containing quick information about home care; and 5- Integrating the website/app with the complete course developed and offered free of charge to informal caregivers. To enable the execution of this work, a partnership was established with E-care+ Sentinela - Multiprofessional Virtual Network for Health Support, the Regional Health Department - DRS XVI-Sorocaba, the Center for Distance Education and Information Technologies in Health (NEAD.TIS-FMB-Unesp), and the Municipality of Itapeva-SP. Results: The sample of interviewees consisted of 30 informal caregivers, predominantly female, composed of children, under 60 years of age, with low levels of education, low income, combining the role of home caregivers and engaging in some activity in the labor market, corroborating studies found in the literature. The listed topics were: 1- Psychosocial aspects of aging; 2- General care; 3- Functional mobility; 4- Medication management; 5- Vital signs monitoring; 6- Diseases of aging; and 7- Care for the caregiver. The online course "Informal Caregiver for the Elderly" was developed on the Moodle platform, structured in didactic modules, containing 6 digital books in E-book format with the topics listed above, 5 podcasts, and 14 videos. At the beginning, the student answered a pre-test assessment, which was repeated at the end of the course. In addition, each didactic module contained its own content assessment. A website and an application were also developed to provide comprehensive support for the daily care routine at home, made available to the general public. The student sample consisted of 23 participants, predominantly female, under 60 years of age, with secondary and higher education levels, acting as informal caregivers for 6 months to 1 year, with a considerable portion having been caregivers for more than 5 years. The participants' final average performance was 9.19 (0-10), indicating that they actively participated in their learning process. Regarding the "pre- and post-tests," a score increase of approximately 14.4% was observed. Final considerations: It is essential to develop support strategies for home caregivers, as well as to create and strengthen a support network for the elderly/caregiver dyad to reduce the burden in the home setting. Health education, through Telehealth, is recommended as a strategy to improve care for the elderly in the home setting. In this study, the educational intervention improved the knowledge of informal caregivers. This research is expected to contribute to the discussion of telehealth practices as a tool for improving the quality of care provided at home. Therefore, this research can serve as a basis for other areas of health education, and the resulting products can be replicated throughout the country.
Training and support network for informal caregivers of the elderly as comprehensive support for care practices at home.
Keywords: Telecuidado; Telessaúde; Cuidador; Cuidador familiar; Cuidadores Informais